Occurrence of antibiotics in mussels and clams from various FAO areas. (1st February 2018) - Chiesa, Luca Maria; Nobile, Maria; Malandra, Renato; Panseri, Sara; Arioli, Francesco
Highlights: A multiclass LC–MS/MS method for 29 antibiotics was developed and validated. Our detection limits were much lower than the maximum residue limits. Pool of mussels and clams from different FAO zones were analysed. Antibiotic presence in the analysed shellfish is negligible. Abstract: Filter feeders, like mussels and clams, are suitable bioindicators of environmental pollution. These shellfish, when destined for human consumption, undergo a depuration step that aims to nullify their pathogenic microorganism load and decrease chemical contamination. Nevertheless, the lack of contamination by drugs may not be guaranteed. Antimicrobials are a class of drugs of particular concern due to the increasing phenomenon of antibiotic resistance. Their use in breeding and aquaculture is a major cause of this. We developed a multiclass method for the HPLC–MS/MS analysis of 29 antimicrobials, validated according to the Commission Decision 2002/657/UE guidelines, and applied it to 50 mussel and 50 clam samples derived from various Food and Agricultural Organisation marine zones. The results obtained, indicate a negligible presence of antibiotics. Just one clam sample showed the presence of oxytetracycline at a concentration slightly higher than the European Union Maximum residue limit set for fish.